Implementasi Undang-undang Demokrasi dan Nilai-nilai urgensitas dalam Kancah Politik Islam di bumi Indonesia - Fatkhiyatus Su’adah; Ahmad Royhan (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2024)
This study examines the implementation and urgency of the Democracy Law in Indonesia. Although democracy is reflected in the 1945 Constitution, Muslim intellectuals often view this concept as foreign. Democratic principles such as majority rule, freedom, and justice face challenges in their application because not all democratic concepts can be reconciled with Islamic law. This research analyzes the interaction between Islamic values, such as benefit and justice, with the democratic principles of the 1945 Constitution and the potential alignment between the two to enhance political stability. The novelty of this study lies in its in-depth comparative analysis between the democratic principles of the 1945 Constitution and the concept of Islamic governance in classical and contemporary fiqh. The method used is a descriptive qualitative approach, analyzing Indonesian legal texts and relevant classical and contemporary fiqh works. The findings indicate the potential for synergy between democratic principles and Islamic values despite challenges in implementation. The application of the Democracy Law in Indonesia requires an approach that is sensitive to religious values, particularly in terms of justice, freedom, and governance based on benefit. Its implications could shift the paradigm of democratic implementation in Indonesia, emphasizing the importance of synergy between state law and religious teachings in creating a just and prosperous government for people.